Studi perilaku campuran aspal berpori terhadap proporsi agregat kasar. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Manajemen Pelayanan Kesehatan, Fak. Kedokteran UGM, 2001)
Porous Asphalt is pavement measure asphalt mix with air void between 15 % - 25 %, which expected can reduce water pool and fixing rub among motor wheel with road surface, specially in rainy season. The experiment has been done in 6 ( six) variation for coarse aggregate, from 53.5 % - 66 % in fixed asphalt portion ( 5 %). There are 3 samples in each coarse aggregate portion. The experiment of stability, cantabro loss, permeability and run of fflow is made to find out Porous Asphalt characteristic. Based on specification, this observation didn't find an optimum air void.